Wireless sensor-free networks for energy usage automation in HDB buildings - Lam, Eric Chun Hao (2016)
‘Smart’ homes are making use of sensors and cameras to detect human activities in the room and thus allowing the electrical appliances to adjust themselves. However, this technique brings about several disadvantages such as the maintenances of the devices. To maintain the devices, it is important to obtain and update the license. Having a license allows the user to obtain signature updates. This way, the device is equipped with the latest software and is up-to-date. At times, it is require to shutdown the sensor for troubleshooting purposes. Also, it is essential to keep the exterior of the devices clean. The dirt may affect the sensors’ or cameras’ capability in sensing or capturing images. In worse case, it may shorten the lifespan of the devices when grime gets in contact with the delicate components. Using camera-based sensor brings about the issue of privacy invasion. These issues can be resolved by adopting a customized wireless sensor-free network.